THE ROLE OF LABORATORY SCIENCE IN NURSING PRACTICE - Savrinov Sodiq Sobirovich; Hakimov Azad Atamuradovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Laboratory science is an indispensable component of modern healthcare, providing critical data for diagnosing, treating, and monitoring diseases. For nurses, understanding laboratory principles and results is essential for patient care, including early detection of illnesses, evaluating treatment efficacy, and educating patients. This article explores the significance of laboratory science in nursing, its applications in various clinical settings, and its role in improving patient outcomes.